An individual iron nanowire-filled carbon nanotube probed by micro-Hall magnetometry - Lipert, Kamil; Bahr, S.; Wolny, F.; Atkinson, P.; Weißker, U.; Mühl, T.; Schmidt, O. G.; Büchner, B.; Klingeler, Rüdiger (Applied physics letters, 2010)
We report on the magnetic properties of an individual, high-quality single-crystalline iron nanowire with diameter - 𝑑=26 nm - d=26 nm - . The nanowire is embedded in a carbon nanotube which provides complete shielding against oxidation. Magnetization reversal is associated with domain wall formation where domain nucleation is initiated by curling. The observed nucleation fields of up to 900 mT are much higher than reported previously and nearly reach the shape anisotropy field of iron nanowires.